**Factorise the expression (a+b)^2=4**

The **factored expression **of the expression given as (a + b)^2 = 4 is (a + b + 2)(a + b - 2) = 0

### What are expressions?

**Expressions** are mathematical statements that are represented by variables, coefficients and operators

### How to factor the expression?

The **expression** is given as

(a + b)^2 = 4

Express 4 as 2^2

So, we have

(a + b)^2 = 2^2

Rewrite as

(a + b)^2 - 2^2 = 0

Apply the **difference **of two squares

So, we have

(a + b + 2)(a + b - 2) = 0

Hence, the **equivalent expression **of the expression given as (a + b)^2 = 4 when it is **factored ** is (a + b + 2)(a + b - 2) = 0

Read more about **expression** at:

#SPJ1

If your question is not fully disclosed, then try using the search on the site and find other answers on the subject Mathematics.

Find another answersMathematics, published 11.05.2023

Mathematics, published 23.03.2023

Use the equation to identify the center and radius of the circle (X+3)^2+(y-7^2=11

Mathematics, published 27.05.2023